TEACHING NARRATIVE TEXT THROUGH COLLABORATIVE STRATEGIC READING TO INCREASE STUDENTS’ READING COMPREHENSION - Natalia, Devi; Arifin, Zainal; ., Husin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Abstract: The purposes of this research are to investigate whether teaching by Collaborative Strategic Reading increase the students’ reading comprehension of narrative text for the tenth grade students of SMA Kemala Bhayangkari 1 Sungai Raya 2013/2014. The form of research is quasy-experimental study. The total numbers of sample are 40 students. The results of data analysis showed based on test t-value, tobserve is bigger than ttable or 11.13> 2.021. It means CSR can increase the students’ reading comprehension. Based on the calculationof Effect Sizevalues, ​​obtained Effect Size of 1.18. This means that Collaborative Strategic Reading have large significantly to improve students’ reading comprehension. It was indicated that the process of teaching and learning influenced the achievement of the students in reading narrative text. Therefore the teaching narrative text by using Collaborative Strategic Reading needs to be applied for the students because it increased the achievement of the students and the students’ interest.   Keywords: Collaborative Strategic Reading, narrative text   Abstrak: Tujuan penelitian ini adalah menyelidiki pembelajaran menggunakan Collaborative Stategic Reading untuk meningkatkan pemahaman membaca teks naratif siswa kelas X SMA Kemala Bhayangkari 1 Sungai Raya 2013/2014. Bentuk penelitian ini adalah studi quasi - eksperimental. Jumlah sampel sebanyak 40 siswa. Hasil analisis data menunjukkan berdasarkan hasil uji t diperoleh tobservasi lebih besar dari ttabel atau11.13 > 2,021. Ini berarti Collaborative Strategic Reading dapat   meningkatkan pemahaman membaca siswa. Berdasarkan perhitungan nilai Effect Size, diperoleh nilai 1.18. Ini berarti bahwa CSR secara signifikan meningkatkan pemahaman membaca siswa. Hal ini menunjukkan bahwa proses pembelajaran mempengaruhi prestasi belajar siswa dalam membaca teks naratif. Oleh karena itu pembelajaran teks naratif menggunakan Collaborative Strategic Reading perlu diterapkan karena dapat meningkatkan prestasi dan minat belajar siswa.   Kata kunci: Collaborative Strategic Reading, Teks Naratif